2010
DOI: 10.2353/ajpath.2010.090194
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Myocilin and Optineurin, Two Glaucoma Genes, on Neurite Outgrowth

Abstract: Myocilin and optineurin are two genes linked to glaucoma , a major blinding disease characterized by progressive loss of retinal ganglion cells (RGCs) and their axons. To investigate the effects of force-expressed wild-type and mutant myocilin and optineurin on neurite outgrowth in neuronal cells , we transiently transfected cells with pEGFP-N1 (mock control) as well as myocilin and optineurin plasmids including pMYOC WT -EGFP, pMYOC P370L -EGFP, pMYOC 1-367 -EGFP, pOPTN WT -EGFP , and pOPTN E50K -EGFP. PC12 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 56 publications
3
37
0
Order By: Relevance
“…4, C and D) as was seen in neurodegenerative diseases (38,50,51). In addition, overexpression of both wild type and E50K optineurin leads to apoptosis in cultured cells (40), and the toxicity can be rescued by rapamycin treatment (Fig. 8C).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…4, C and D) as was seen in neurodegenerative diseases (38,50,51). In addition, overexpression of both wild type and E50K optineurin leads to apoptosis in cultured cells (40), and the toxicity can be rescued by rapamycin treatment (Fig. 8C).…”
Section: Discussionmentioning
confidence: 59%
“…After transfection with wild type or E50K optineurin, the optineurin foci are observed to distribute in the perinuclear region in proximity to the Golgi complex (17,18,40). Following precedent of those described for aggresomes, inclusion bodies, or Lewy bodies, the optineurin foci are formed in a microtubule-dependent manner (17,18).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…On the contrary, Koga et al 73 recently showed that overexpression of wild-type OPTN results in increased apoptosis of RGCs and that OPTN (wild type or the E50K mutant form), unlike MYOC, is devoid of effects on neurite outgrowth in neuronal cells. They concluded that MYOC and OPTN appear to have different functions and may contribute to the development of neurodegenerative glaucoma via distinct mechanisms, which are still largely unknown.…”
Section: Myoc Protein and Glaucoma Pathogenesismentioning
confidence: 99%
“…Koga et al 73 demonstrated that overexpression of wild-type MYOC or P370L and Q368X mutants, but not OPTN, caused an inhibition of neurite outgrowth and thus may contribute to the development of neurodegenerative glaucoma. 73 OPTN at the GLC1E locus The second gene associated with POAG was identified in 2002 and it was given the name OPTN (OPTN for optic neuropathy-inducing protein) by Rezaie et al 9 An adult-onset POAG locus had been previously mapped on chromosome 10p14-p15, the GLC1E locus, in a linkage study of a large British family in which 15 of 46 family members were affected with NTG. 10 After excluding four genes, Rezaie et al 9 selected OPTN as a candidate gene on the basis of its physical location in this region and its expression in retina.…”
Section: Myoc Protein and Glaucoma Pathogenesismentioning
confidence: 99%